Edible Plants of the Prairie - Kelly Kindscher (Symphony in the Flint Hills, 2009)
Sitting here, in this spot, in the prairie, looking across this beautiful Flint Hills landscape, one sees a diversity of plants, grasses, and wildflowers, many of which were profoundly important as food and medicines for the people who lived here before. The Great Plains has more than 3,000 plant species, and more than 120 species were used by Native Americans for food, seasonings, tea, health, and nutrition.
Keywords: edible; plants; grasses; flowers; prairie turnip; plains; Native Americans; tea; herbs; poisonous; life; herbal; remedy; wildflowers; cure; tribe; tribal; medicine; food; anthropologists; Plum; sunflower; artichoke; groundnut; onion; milkweed; Lambsquarters